2000
DOI: 10.1016/s0264-8172(00)00035-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Cenozoic erosion from mean sonic transit time, offshore Taiwan

Abstract: Mean sonic transit times from eight stratigraphic units in forty-four wells in western and northern offshore Taiwan were plotted against depth. Apparent erosion (displacement on the depth axis from the normal compaction) was determined for each unit in each well. Cretaceous and Eocene units show greater apparent erosion than Miocene and Pliocene units in the same well, which in turn show more erosion than Pleistocene units. Apparent erosions derived from two different units are plotted against each other for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…The characteristics of periodic coarsening upward sequences indicate a strong tectonic signature that can be comparable to other examples in some tectonically active belts [9,10,11]. The tectonic origin for the unconformities is also supported by the calculated magnitude of erosion of the unconformities in the Plio-Pleistocene [98], which scale is larger than that could be caused by eustatic sea level fall during the same period. The well bore data was correlated to a seismic line tied to the well and the interpreted seismic profile shows that the sequence boundaries are characterized by prominent canyon morphology to the south of the well site ( Figure 9).…”
Section: Sedimentology Of Sequence Boundariessupporting
confidence: 65%
“…The characteristics of periodic coarsening upward sequences indicate a strong tectonic signature that can be comparable to other examples in some tectonically active belts [9,10,11]. The tectonic origin for the unconformities is also supported by the calculated magnitude of erosion of the unconformities in the Plio-Pleistocene [98], which scale is larger than that could be caused by eustatic sea level fall during the same period. The well bore data was correlated to a seismic line tied to the well and the interpreted seismic profile shows that the sequence boundaries are characterized by prominent canyon morphology to the south of the well site ( Figure 9).…”
Section: Sedimentology Of Sequence Boundariessupporting
confidence: 65%
“…From the Late Eocene to the Oligocene the foreland area in western Taiwan encountered differential uplifting and formed a large-scale regional unconformity. During this period, the 3000-3500 m thick Paleogene strata were eroded on the Peikang-Penghu Basement High (Fuh, 2000), and the greater uplift to the south resulted in the complete erosion of Paleogene strata in that area. From the beginning of the Late Oligocene, the foreland area in western Taiwan encountered differential subsidence that formed two Neogene basins now separated by the Peikang-Penghu Basement High (Meng, 1971;Sun, 1982).…”
Section: Regional Tectonic Modementioning
confidence: 99%
“…The eroded sediment thickness based on seismic data increases from north to south, which is about 250 m in the Wenzhou Sag, lying to the north of the Lishui Sag, and about 600 m in the Lishui Sag [ Wang , 1991]. On the basis of the sonic velocity versus depth relationship, Fuh [2000] concluded that on the Pengchiahsu Platform, the maximum erosion at the Oligocene unconformity was 2500 m, while it was 2000–3500 m in the West Taiwan basins. On the basis of the same kind of data, Lin et al [2003] estimated that the erosion in the area ranged from 1000 m to 3000 m, and the maximum erosion could accumulate to 4500 m on the Penghu Platform.…”
Section: Data and Observationsmentioning
confidence: 99%
“…The uplift and erosion event is not simply the result of eustasy, but caused by tectonic events. The change of global sea level in the Oligocene is about 200 m, which would at most cause 1000 m erosion based on local isostasy and cannot account for more than 3 km erosion, as mentioned above [ Fuh , 2000; Lin et al , 2003; Wang et al , 1995]. As shown in Figure 2, in the late Eocene and Oligocene, there were some strong tectonic events, for example, the Zhuqiong II event (in the late Eocene) and the Nanhai event (∼30 Ma, Breakup unconformity) in the Pearl River Mouth, the Puli event (37–30 Ma [ Lin et al , 2003]) in the West Taiwan Basin, and the Yuquan event (in the late Eocene) and Huagang event (in the late Oligocene) in the East China Basin.…”
Section: Data and Observationsmentioning
confidence: 99%